Takanab and Human Dignity According to the Dawan Society - Ikun, Sekundus; Vianey, Yohanes Watu; Naif, Oktovianus (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2021)
Humans are unique creatures, they were created in the image and likeness of God. Humans are also highly noble creatures because humans have the dignity of reason, conscience and the nobility of freedom to preserve God's other creations. Humans are creatures that exist because they have consciousness, through this consciousness humans establish relationships with God, nature and fellow humans. Human life always exists with others because through others each individual can know who he really is. In this togetherness, humans maintain what is considered good in the collective life of society, which is called tradition. In the context of the archipelago, the Dawan people in Timor, East Nusa Tenggara know an oral tradition, namely the Takanab for picking up new priests. Takanab for picking up a new priest is a traditional speech spoken by traditional elders or mavefa (speakers) when picking up a new preist. The fundamental question of this cultural study is why humans should be respected? This research uses qualitative research methods to collect and analyze data. Based on data obtained through literature review and interviews, there are new findings regarding the Takanab tradition of picking up new priest. In the Takanab tradition, it is not only an expression of gratitude to the ancestors and God, but also human dignity is highly upheld. Human dignity in the Takanab tradition of picking up new priests is one of the new variants that needs to be developed and must be supported by government institutions and religious institutions (Catholics) so that there is harmonious inculturation in living together.